Superficial vein thrombosis in non-varicose veins of the lower limbs and thrombophilia. (May 2018) - Lucchi, Gabriella; Bilancini, Salvino; Tucci, Sandro; Lucchi, Massimo
Objectives: Superficial vein thrombosis in non-varicose veins of the lower limbs is rather frequent and may be underestimated. This study aims to evaluate the prevalence of inherited or acquired thrombophilia in a sample of outpatients with the disease. Method: An observational study was conducted on 73 consecutive superficial vein thrombosis patients tested for inherited or acquired thrombophilia. Results: Sixty of 73 patients with superficial vein thrombosis completed the testing protocol, while 13 dropped out; 46 of 60 patients were found to have a thrombophilia (76.6%). The types detected were: factor V Leiden (31/60, i.e. 51.6%), prothrombin mutation (2/60, i.e. 3.3%), MTHFR mutation (23/60, i.e. 38.3%), antiphospholipid antibodies (5/60, i.e. 8.3%), protein C deficit (1/60, i.e. 1.6%), protein S deficit (1/60, i.e. 1.6%), and antithrombin deficit (0/60, i.e. 0%). Conclusions: Among patients with superficial vein thrombosis in non-varicose veins, testing demonstrated a high prevalence of thrombophilia. The most common form proved to be factor V Leiden. As thrombophilia was found to be a major cause of superficial vein thrombosis in non-varicose veins, the authors recommend that patients with superficial vein thrombosis in non-varicose veins be investigated for thrombophilia.